THE INFLUENCE OF GADGETS ON THE DEVELOPMENT OFPRIMARY SCHOOL CHILDREN: THE IMPORTANCE OF PROPEREDUCATION: PENGARUH GADGET TERHADAP PERKEMBANGAN ANAKSEKOLAH DASAR: PENTINGNYA EDUKASIYANG TEPAT - Azizah, Alya Nur (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The rapid development of technology, especially in gadgets, has influenced various aspects of life,including among students. Excessive use of gadgets can hurt students' physical and mental health. This research aims to provide education about the negative impacts of excessive use of gadgets on students at school. The method used is counseling through seminars and interactive discussions to increase students' understanding of potential health risks and psychological disorders due to dependence on gadgets. The research results show that this counseling can increase students' awareness of the importance of using gadgets wisely and healthily, as well as its impact on their lives. Therefore, it is hoped that this counseling can make a positive contribution to forming healthy habits among students in using gadgets.